Selecting the appropriate hurdles and endpoints for pentilludin, a novel antiaddiction pharmacotherapeutic targeting the receptor type protein tyrosine phosphatase D - Uhl, George R. (Frontiers in Psychiatry, 2023)
Substance use disorders provide challenges for development of effective medications. Use of abused substances is likely initiated, sustained and “quit” by complex brain and pharmacological mechanisms that have both genetic and environmental determinants. Medical utilities of prescribed stimulants and opiates provide complex challenges for prevention: how can we minimize their contribution to substance use disorders while retaining medical benefits for pain, restless leg syndrome, attention deficit hyperactivity disorder, narcolepsy and other indications. Data required to support assessments of reduced abuse liability and resulting regulatory scheduling differs from information required to support licensing of prophylactic or therapeutic anti-addiction medications, adding further complexity and challenges. We describe some of these challenges in the context of our current efforts to develop pentilludin as a novel anti-addiction therapeutic for a target that is strongly supported by human and mouse genetic and pharmacologic studies, the receptor type protein tyrosine phosphatase PTPRD.